Diversifikasi Manfaat Rimpang Temulawak sebagai Komponen Aktif terhadap Bakteri Streptococcus Mutans pada Pembuatan Permen Kesehatan - Medan Yumas (Jurnal Riset Teknologi Industri, 2016)
The research to utilization of ginger rhizome as active component on Streptococcus mutants in the manufacture of oral health candy have been carried out.  The aim of this research is to produce health candies with containing the main active component of ginger oil.  These components can serve as anti bacterial, anti inflammatory, and can neutralize acid in the mouth.  Ginger oil contain main active components known as xanthorrizol.  The result showed that the minimum inhibitory concentration again is Streptococcus mutants was 0,25%, (bacteriostatic) and minimum kill concentration was 0,40% (bakterisid).  The addition of ginger oil in the manufacture of health candies was done by varying the concentration 0,40%, 0,55%, 0,70%, 0,85% and 1 % (b/b).  Candy health with the addition of 0,85% concentration of ginger oil can kill the bacteria Streptococcus mutants in one minute and have power zone of inhibition 15,89 mm.  This type of candy is the most preferred health by panelist.